Comparison Of The Legal Perspective Of The Kutai Customary Court (Dayak Tribe) With Positive Criminal Law On The Crime Of Murder - Bastoni Purnama; Ade Saptomo (Hakim, 2024)
The lives of traditional law communities in Indonesia reflect the cultural diversity and traditional riches of various ethnic groups. This research discusses the application of positive criminal law to criminal acts of murder in Indonesia, with a focus on the West Kutai traditional tribe, the majority of whose population comes from the Dayak tribe. This research uses normative legal methodology or library research. The results of this research describe the application of positive criminal law to criminal acts of murder, the classification of these criminal acts based on error factors and their objects, as well as the Dayak tribe's perspective on murder cases using Sutherland's criminological theory.